AN ERROR ANALYSIS OF STUDENTS' GRAMMATICAL MISTAKES BASED ON CONTRASTIVE ANALYSIS - Sabrina Salsabila; Siti Ismahani; Nadhifa Shofi Andara; Nurul Fadilah Tambunan; Celli Geovani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Grammatical errors remain a major challenge for English as a Foreign Language (EFL) learners in Indonesian higher education. However, studies integrating Error Analysis (EA) and Contrastive Analysis (CA) to identify the sources of errors in the context of Islamic higher education remain limited. This study aims to analyze the grammatical errors made by EFL students through a combined EA and CA approach. A mixed-methods design was employed involving 20 students from the TBI-3 class of the 2023 cohort at the State Islamic University of North Sumatra (UINSU), Medan. Data were collected through essay-writing tasks and analyzed using both quantitative and qualitative methods. The findings revealed 300 grammatical errors across six major categories, with subject–verb agreement errors being the most dominant. Most errors were influenced by first-language transfer (Indonesian), supporting the predictions of Contrastive Analysis regarding cross-linguistic influence in second-language acquisition. Inter-rater reliability demonstrated a high level of agreement (κ ≥ 0.81). These findings confirm that the integration of EA and CA is effective in identifying patterns of grammatical errors and can serve as a basis for developing more targeted grammar instruction for Indonesian EFL learners. ABSTRAK Kesalahan gramatikal masih menjadi kendala utama bagi pembelajar bahasa Inggris sebagai bahasa asing (EFL) di perguruan tinggi Indonesia. Namun, penelitian yang mengintegrasikan Analisis Kesalahan (Error Analysis/EA) dan Analisis Kontrastif (Contrastive Analysis/CA) untuk mengidentifikasi sumber kesalahan dalam konteks perguruan tinggi Islam masih terbatas. Penelitian ini bertujuan menganalisis kesalahan gramatikal mahasiswa EFL melalui pendekatan gabungan EA dan CA. Penelitian menggunakan metode campuran (mixed methods) dengan melibatkan 20 mahasiswa kelas TBI-3 Angkatan 2023 di Universitas Islam Negeri Sumatera Utara (UINSU), Medan. Data diperoleh melalui tugas menulis karangan dan dianalisis secara kuantitatif serta kualitatif. Hasil penelitian menunjukkan terdapat 300 kesalahan gramatikal dalam enam kategori utama, dengan kesalahan kesesuaian subjek-predikat sebagai bentuk yang paling dominan. Sebagian besar kesalahan dipengaruhi oleh transfer bahasa pertama (Bahasa Indonesia), sehingga mendukung prediksi Analisis Kontrastif mengenai pengaruh lintas bahasa dalam pemerolehan bahasa kedua. Reliabilitas antarpenilai menunjukkan tingkat kesepakatan yang tinggi (κ ≥ 0,81). Temuan ini menegaskan bahwa integrasi EA dan CA efektif untuk mengidentifikasi pola kesalahan gramatikal serta dapat menjadi dasar pengembangan pembelajaran tata bahasa yang lebih tepat bagi pembelajar EFL Indonesia.